Study on the impact parameters of convective heat transfer in industrial-scale Siemens reactor - Xingping Yuan; Dan Zhao; Yanqing Hou; Ni Yang; Wenhui Ma; Fengyang Chen; Gang Xie (Case Studies in Thermal Engineering)
In industrial-scale Siemens reactors, convective heat transfer (CHT) plays a crucial role in regulating the uniformity of the reactor's temperature distribution and ensuring the quality of the polysilicon products. This study developed a forced CHT model for a 12-pair silicon rod industrial-scale Siemens reactor. The effects of operating parameters (inlet gas temperature, inlet gas velocity and silicon rod surface temperature) and geometrical parameters (diameter and number of silicon rods) on the CHT coefficient were analyzed, and the results indicate that the inlet gas velocity and the diameter of the silicon rods had the greatest effect on the CHT coefficient, which fluctuated up to. 85.5 W m⁻2 K⁻1. Furthermore, this study also considered the interactions between these factors and derived a correlation equation that characterizes the CHT behavior in the reactor. The equation was validated using production data from a 24-pair silicon rod industrial-scale Siemens reactor, with an error of only 7.6 %, demonstrating the reliability of the model. Consequently, the established forced CHT model and correlation equation can effectively predict CHT in industrial-scale Siemens reactors. This study provides a valuable tool for optimizing reactor design and operation, ultimately contributing to the reduction of silica fines formation and energy consumption during the production process.